Analysis of the Impact of the E-Commerce Phenomenon on Product Sales in Malang's Big Market - Linda Nur Afifa; Vitri Yuniarti; Azhar Arkho (International journal of technology and education research, 2026)
This research is motivated by the rapid development of e-commerce, which has influenced trading activities in traditional markets, including Pasar Besar Malang. This study aims to analyze the impact of the e-commerce phenomenon on clothing sales in Pasar Besar Malang and identify changes in consumer behavior and trader adaptation strategies. The study used a qualitative approach with a descriptive phenomenological method. The study population consisted of clothing traders and consumers in Pasar Besar Malang, with a sample of 15 informants selected through purposive and snowball sampling. The research instruments included semi-structured interviews, observation, and documentation. Data analysis techniques used the interactive model of Miles, Huberman, and Saldana through data reduction, data presentation, and conclusion drawing. The results show that the development of e-commerce has caused a decrease in the number of buyers, sales turnover, and social interactions in traditional markets due to changes in consumer preferences towards more practical and efficient online shopping. This study concludes that e-commerce has a significant economic and social impact on the sustainability of traditional markets, so that digital adaptation strategies, improved market facilities, and government support are needed so that traders can remain competitive in the digital era.